International Agreements, Economic Sovereignty and Exit - Martin Richardson; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2018)
We develop a model in which it is uncertainty about the future domestic policy environment that both makes international cooperation attractive and induces the possibility of a nation reneging on such an international agreement. We show, in a fairly general setting in which the likelihood of exit is affected by the degree of cooperation, that the possibility of exit reduces the optimal degree of initial cooperation. “Full” cooperation will never be optimal, and the optimal degree of cooperation will never be such as to “squeeze out” any possibility of exit. However, an increase in global uncertainty may imply an increase in cooperation when exit risks are already large to begin with.
Keywords: F02; F13; F51; F53; 330; international agreements; international cooperation; exit; sovereignty